A Thorny Path $1 (BVolume 03s - Ebers, Georg, 1837-1898; Bell, Clara, 1834-1927 (Salt Lake City, UT : Project Gutenberg, 2004)
"A Thorny Path $1 (BVolume 03" by Georg Ebers is a historical novel written in the late 19th century. The book is set in ancient Alexandria during a time when conflicts arise between different belief systems, particularly between emerging Christianity and traditional paganism. It likely explores themes of love, faith, sacrifice, and the struggles faced by individuals caught in the midst of societal changes. In this volume, the narrative focuses on Melissa and Andreas as they grapple with the dire circumstances surrounding Melissa's betrothed, Diodoros, who is gravely injured and in need of a renowned physician. Their paths lead them through the bustling streets of Alexandria, where various social and political dynamics unfold. Melissa's determination to seek help for Diodoros reveals her strong character and highlights the conflicts of loyalty and faith that Andreas faces, as he struggles between supporting her wishes and maintaining his own moral convictions. The intricate relationships and societal pressures give rise to moments of tension and soul-searching, ultimately building towards pivotal decisions that will impact their lives and the lives of those around them. (This is an automatically generated summary.)s
Release date is 2004-04-01
This eBook was produced by David Widger
Keywords: Egypt -- History -- 30 B.C.-640 A.D. -- Fiction; German fiction -- Translations into English